2005
DOI: 10.1111/j.1399-5618.2004.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder and myo‐inositol: a review of the magnetic resonance spectroscopy findings

Abstract: The preclinical and clinical MRS findings were generally supportive of the involvement of myo-inositol in bipolar disorder and its treatment. Overall, in bipolar patients who are manic or depressed there are abnormalities in brain myo-inositol concentrations, with changes in frontal and temporal lobes, as well as the cingulate gyrus and basal ganglia. These abnormalities are not seen in either euthymic patients or healthy controls, possibly due to a normalizing effect of treatment with either lithium or sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
2
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 68 publications
1
77
2
4
Order By: Relevance
“…Furthermore, bipolar mood disorder has a strong genetic predisposition but is a complex genetic trait that probably involves combinations of multiple loci (Craddock and Jones, 1999). As yet, no susceptibility gene has been unambiguously identified but, interestingly, many of the candidate genes currently under investigation converge on the PIP 3 -and PKB-mediated signal pathway (Silverstone et al, 2005;Carter, 2007). The results presented here provide a mechanism that might directly couple current genetic studies with a target of lithium therapy.…”
Section: Research Reportmentioning
confidence: 80%
“…Furthermore, bipolar mood disorder has a strong genetic predisposition but is a complex genetic trait that probably involves combinations of multiple loci (Craddock and Jones, 1999). As yet, no susceptibility gene has been unambiguously identified but, interestingly, many of the candidate genes currently under investigation converge on the PIP 3 -and PKB-mediated signal pathway (Silverstone et al, 2005;Carter, 2007). The results presented here provide a mechanism that might directly couple current genetic studies with a target of lithium therapy.…”
Section: Research Reportmentioning
confidence: 80%
“…Among those, inhibition of the inositol monophosphatase was suggested to be a common mechanism of action of three mood stabilizers (Williams et al, 2002). Inhibition of the inositol monophosphatase has been shown to increase inositol monophosphates and to decrease myoinositol concentrations in rat brain (O'Donnell et al, 2000), although in humans, this effect has not consistently been observed (Silverstone et al, 2005). In our study, chronic lithium treatment did not result in significant changes in the levels of those inositol phosphates that have specific roles in cell signalling (Table 3 and Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have since demonstrated the validity of this hypothesis as an explanation for the therapeutic action of lithium; magnetic resonance spectroscopy (MRS) findings have shown abnormal PI-cycle activity and elevated myo-inositol concentrations in patients with bipolar disorders [Silverstone et al 2005], thus it follows that lithium potentially exerts a therapeutic effect by affecting cell signalling as a result of IMPase inhibition, and subsequent reduction of elevated inositol and phosphatidylinositol levels [Haimovich et al 2012]. …”
Section: Lithium and The Phosphatidylinositol Signalling Pathwaymentioning
confidence: 99%
“…Within the PI signalling pathway (Figure 1), the enzyme IMPase typically regenerates myoinositol from inositol monophosphates, which in turn leads to the resynthesis of phosphatidylinositol [Silverstone et al 2005]. At therapeutically relevant doses, lithium is a potent inhibitor of various phosphoinositol phosphates involved in inositol phosphate metabolism, including the intracellular enzymes IMPase and inositol polyphosphatase 1-phosphatase (IPP 1) [Allison and Stewart, 1971;Phiel and Klein, 2001]; this inhibition leads to inositol depletion, a consequential reduction in the resynthesis of phosphatidylinositol bisphosphate (PIP2) and prevents regeneration of the second messenger inositol-1,4,5, triphosphate (IP3) [Phiel and Klein, 2001], with subsequent effects on signal transduction [Haimovich et al 2012].…”
Section: Lithium and The Phosphatidylinositol Signalling Pathwaymentioning
confidence: 99%